Regulation of the Dimerization and Activity of SARS-CoV-2 Main Protease through Reversible Glutathionylation of Cysteine 300 - Davis, David A; Bulut, Haydar; Shrestha, Prabha; Yaparla, Amulya; Jaeger, Hannah K; Hattori, Shin-Ichiro; Wingfield, Paul; Mitsuya, Hiroaki; Yarchoan, Robert (bioRxiv, 2021)
SARS-CoV-2 encodes main protease (Mpro), an attractive target for therapeutic interventions. We show Mpro is susceptible to glutathionylation leading to inhibition of dimerization and activity. Activity of glutathionylated Mpro could be restored with reducing agents or glutaredoxin. Analytical studies demonstrated that glutathionylated Mpro primarily exists as a monomer and that a single modification with glutathione is sufficient to block dimerization and loss of activity. Proteolytic digestions of Mpro revealed Cys300 as a primary target of glutathionylation, and experiments using a C300S Mpro mutant revealed that Cys300 is required for inhibition of activity upon Mpro glutathionylation. These findings indicate that Mpro dimerization and activity can be regulated through reversible glutathionylation of Cys300 and provides a novel target for the development of agents to block Mpro dimerization and activity. This feature of Mpro may have relevance to human disease and the pathophysiology of SARS-CoV-2 in bats, which develop oxidative stress during flight.